Test Scores, Noncognitive Skills and Economic Growth - Pau Balart; Matthijs Oosterveen; Dinand Webbink (Institute for the Study of Labor (IZA), 2015)
Many studies have found a strong association between economic outcomes of nations and their performance on international cognitive tests. This association is often interpreted as evidence for the importance of cognitive skills for economic growth. However, noncognitive skills, such as motivation and perseverance, are also important for the performance on cognitive tests. This study decomposes the performance on an international test (PISA) into two components that differ with respect to their underlying skills: the starting level and the decline in performance during the test. The first component can be interpreted as a measure of cognitive skills, whereas the second component captures noncognitive skills. We find that countries differ in the starting level and in the decline in performance, and that these differences are stable over time. Both components have a positive and statistically significant association with economic growth, and the estimated effects are quite similar. This suggests that noncognitive skills are important for explaining the relationship between test scores and economic growth.
Keywords: J24; 330; cognitive skills; noncognitive skills; long run economic growth